Plain language summary of the MAIA study of daratumumab plus lenalidomide and dexamethasone for the treatment of people with newly diagnosed multiple myeloma - Facon, Thierry; Kumar, Shaji K; Plesner, Torben; Orlowski, Robert Z; Moreau, Philippe; Bahlis, Nizar; Basu, Supratik; Nahi, Hareth; Hulin, Cyrille; Quach, Hang; Goldschmidt, Hartmut; Perrot, Aurore; et al. (Future oncology, 2023)
What is this summary about? - - This is a summary of a clinical trial called MAIA. The trial tested 2 combinations of cancer drugs (daratumumab plus lenalidomide and dexamethasone compared with lenalidomide and dexamethasone) in people with newly diagnosed multiple myeloma. None of the participants who took part in the study had been treated before or were eligible to receive stem-cell transplants. - - How was the study in this summary conducted? - - A total of 737 participants took part. Half of the participants took daratumumab plus lenalidomide and dexamethasone, while the other half of the participants took only lenalidomide and dexamethasone. Once participants started taking the drugs, the cancer was monitored for improvement (response to treatment), worsening (disease progression), or no change. Participants' blood and urine were tested for myeloma protein to measure response to the treatment. Participants were also monitored for side effects. - - What were the results of the study? - - After approximately 56 months of follow-up, more participants who took daratumumab plus lenalidomide and dexamethasone were alive and had decreased myeloma protein levels (indicating improvement of cancer) than participants who took only lenalidomide and dexamethasone. The most common side effects were abnormally low white and red blood cell counts and increased lung infections. - - What do the results of the study mean? - - In the MAIA study, participants with multiple myeloma who took daratumumab plus lenalidomide and dexamethasone lived longer and had decreased myeloma protein levels than participants who took only lenalidomide and dexamethasone, indicating survival could be more likely with daratumumab added. - - Clinical Trial Registration:NCT02252172 (Phase 3 MAIA study)